Evaluasi Efektivitas Kinerja Instalasi Pengolahan Air Limbah (IPAL) di Kota Surakarta - Rizky Nugraha Ramadhan; Budi Utomo; Solichin Solichin; Cahyono Ikhsan; Koosdaryani Soeryodarundio (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2024)
Household sewage treatment in Surakarta City depends on the performance of the available domestic wastewater treatment plants (IPAL), including Pucangsawit IPAL, Semanggi IPAL, Mojosongo IPAL, and UNS IPAL. Each of these IPAL’s serves a specific area, such as the UNS IPAL which serves the UNS area and its surroundings, the Mojosongo IPAL which is in charge of the North Area of Surakarta, the Semanggi IPAL which takes care of the South Area of Surakarta, and the Pucangsawit IPAL which serves the Central Area of Surakarta City. This research aimed at the effectiveness of the performance and development plan of each IPAL in the next 20 years. This research used descriptive qualitative and quantitative analysis methods. Qualitative descriptive analysis was conducted by observing the existing condition of IPAL Komunal in the research location. Quantitative descriptive analysis in this study was carried out by testing samples at the inlet, aeration, and outlet points of the IPAL. Based on the quality standards of the Minister of Environment and Forestry Regulation number P 68 of 2016, each IPAL. UNS IPAL is 47.27% for BOD, 73.81% for COD, 76.36% for TSS. Mojosongo IPAL is 88.71% for BOD, 76.50% for COD, 78.57% for TSS. Pucangsawit IPAL was 91.88% for BOD, 83.20% for COD, 74.82% for TSS. Semanggi IPAL is 20.45% for BOD, 69.95% for COD, 69.05% for TSS. Alternative development at the IPAL that can be done to prepare for the next 20 years is to increase the volume in the initial settling basin, aerobic biofilter basin, and also the final settling basin.